Konstruksi Emosi dan Narasi melalui Teknik Editing dalam Film “Ada Apa denganCinta?”: Analisis Visual dan Naratif dalam Konteks Sinema Modern Indonesia - Dr. RR Ella Evrita H, S.E, M.M,, Dr. RR Ella Evrita H, S.E, M.M,; Dewi Alibasah, Dewi Alibasah (Profilm Jurnal Ilmiah Ilmu Perfilman dan Pertelevisian, 2024)
The study examines the editing techniques used in the film "What's with Love?" (AADC) and how the technique affects the development of emotions, narratives, and character development. The film, released in 2002, became a milestone in the revival of Indonesian cinema post-reform, and had a significant impact on the development of youth films in Indonesia. This study investigates how continuity editing, montage, cross-cutting, and the use of music successfully create a cohesive and emotional narrative through a qualitative approach and visual-narrative analysis. AADC's editing techniques not only structured the storyline, but also deepened the characterization and increased the intensity of the conflict. This study found that the editing techniques in AADC successfully overcame the complicated editing process, especially with the limitations of the technology at the time, by using advanced technology such as AVID Media Composer, as well as accurate editing methods to ensure perfect synchronization between the digital version and the celluloid film.